Cross-cultural translation, validity, and reliability of the French version of the Neurophysiology of Pain Questionnaire. (2nd November 2017) - Demoulin, Christophe; Brasseur, Pauline; Roussel, Nathalie; Brereton, Clara; Humblet, Fabienne; Flynn, Daniel; Van Beveren, Julien; Osinsky, Thomas; Donneau, Anne-Françoise; Crielaard, Jean-Michel; Vanderthommen, Marc; Bruyère, Olivier
ABSTRACT: Pain physiology education is an important component in the management of patients with chronic musculoskeletal pain. The Neurophysiology of Pain Questionnaire (NPQ) was developed in English to assess pain physiology knowledge in patients. This study aimed to translate the NPQ into French (NPQ-Fr) and to investigate the main psychometric properties of the NPQ-Fr. The translation was performed using the best practice translation guidelines. One hundred and one French-speaking patients with chronic non-specific spinal pain completed the NPQ-Fr to assess its acceptability and presence of floor/ceiling effects and test its dimensionality. The construct validity was tested by comparing the patients' NPQ-Fr scores to those of 17 physiotherapists and investigating its correlation with subscales of the Short Form-36 questionnaire. The reliability (i.e., internal consistency and test-retest reliability) was also investigated. To test the test-retest reliability, 70 patients were asked to complete the NPQ-Fr twice with one week in between. Regarding the NPQ-Fr psychometric properties: 1) acceptability was good; 2) internal consistency reached a Cronbach α-coefficient of 0.44; 3) no floor and ceiling effects were observed in patients; 4) a principal factor analysis generated three major factors; 5) construct validity was good; and 6) reliability was acceptable (intraclass correlation coefficient = 0.644; standard error of measurement = 1.5). The NPQ-Fr has satisfactory basic psychometric properties in patients with chronic spinal pain.